Effect of Multi-Wall Carbon Nanotubes on the Microhardness of the Tooth Enamel - Mohammed K. Jawad1, Abbas F. Ali2, Ali B. Roomi3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: The object of this study was to investigate the effect of addition of Multi-Wall Carbon Nano Tubes (MWCNTs) in different concentration (0.001g/20ml, 0.005g/20ml , 0.01g/20ml and 0.02g/20ml) in (dimethyl sulphoxide) to tooth enamel. It is intended to evaluate enamel hardness in (Kg .m-2) before and after the addition of (MWCNTs). Materials and Method: Thirty specimens were prepared for this study, to measure the hardness of the enamel. Results: The results enamel hardness after MWCNTs application With DMSO showed a significant increase (P<0.01) between groups of 0.001g/20ml , 0.005 g/20ml , 0.01 g/20ml and , 0.02 g/20ml concentration compared with control group. Where the highest mean value obtained was in 0.02g/20ml concentration which had a mean value of 527.18 ± 2.904 Kg .m-2 , while the lowest mean value was for control group which had a mean value of 334.87± 2.904 Kg .m-2. Polished enamel surface groups showed a significant increase 452.59 ± 1.84 Kg .m-2 (P<0.01) in hardness when compared with unpolished enamel surface groups 430.16 ± 1.84 Kg .m-2 (P<0.01). Conclusion: The highest mean value obtained was in 0.02g/20ml concentration in the hardness suspended in DMSO. The results showed a significant increase in the hardness for polished enamel surface samples compared with unpolished enamel surface samples in DMSO.